Job and Life Satisfaction of Teaching Personnel in a State University in Quezon Province - Leomar Miano, (Technium Social Sciences Journal, 2020)
This study aimed to explore the relationship between Job and Life Satisfaction of Teaching Personnel in a State Southern University in Quezon Province. Data from 204 teaching personnel were collected through purposive sampling. The quasi-descriptive-correlational design was used in this study. Weighted mean correlation coefficient used in the interpretation of data. Based on the findings the conclusions are presented as follows: The teaching personnel was satisfied with the compensation and benefits, promotion, supervisory practices, and working condition. Therefore, the teaching personnel at a State University in Quezon Province were "Satisfied" on their job. Furthermore, the teaching personnel is satisfied with the family, health, social relationship, and work. Consequently, the teaching personnel at a State University in Quezon Province were "Satisfied" in their lives. Moreover, there was a significant relationship between job satisfaction and life satisfaction. The result also shows that there was a significant difference in job satisfaction according to age, civil status, and tenure and there was a significant difference in life satisfaction according to gender, civil status, and tenure.